(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The phenomenon of colloquial metaphor in Spanish is explored. The difference between a linguistic metaphor and a speech metaphor is determined. Effective thematic groups of metaphors that work in the conversational style of the Spanish language have been identified. The variety of functions of colloquial metaphor is shown using specific linguistic material.